Suppression of Retinal Neovascularization by Inhibition of Galectin-1 in a Murine Model of Oxygen-Induced Retinopathy - Ning Yang; Wenxi Zhang; Tao He; Yiqiao Xing (Journal of Ophthalmology)
Galectin-1 (Gal-1) has been proved to be an important factor in the process of tumor angiogenesis recently. As a small molecule, OTX008 serves as a selective inhibitor of Gal-1. In this study, the role of Gal-1 and the antiangiogenic effect of OTX008 on retinal neovascularization (RNV) were investigated using a mouse model of oxygen-induced retinopathy. The outcome indicated that Gal-1 was overexpressed and closely related to retinal neovessels in OIR. After intravitreal injection of OTX008 at P12, the RNV was significantly reduced at P17, measuring by cross-sectional H&E staining and whole-mount fluorescence. Our results demonstrate the inhibitory function of OTX008 on RNV, which provides a promising strategy of treating retinal angiogenic diseases such as retinopathy of prematurity and proliferative diabetic retinopathy.